A Visible‐Light‐Induced Dynamic Mechanical Bond as a Linkage for Dynamic Materials. Issue 36 (5th August 2019) - Yin, Yong‐Fei; Yun, Meng‐Yan; Wu, Lin; Duan, Hong‐Ying; Jiang, Xia‐Min; Zhan, Tian‐Guang; Cui, Jiecheng; Liu, Li‐Juan; Zhang, Kang‐Da
Abstract: Exploring dynamic bonds and their applications in fabricating dynamic materials has received great attention. A photoinduced [2]rotaxane‐based dynamic mechanical bond (DMB) features visible‐light‐triggered dynamic bonding behavior that is essentially distinguished from conventional dynamic chemical bonds. In this DMB, a photoisomerizable ortho ‐fluoroazobenzene unit is introduced as a steric‐controllable stopper, the visible‐light‐induced dynamic wagging movement of which enables the photoregulated threading of the macrocycle. This allows reversible in situ de‐/reforming of the mechanical bond without involving dynamic chemical linkage. The DMB‐cross‐linked polymeric gel shows interesting photoinduced degradation behavior upon visible light irradiation. Benefiting from the distinctive dual dynamic nature of reversible bonding behavior and mechanical interlocked structure, this DMB is expected to serve as a new type of dynamic bond that can be applied in designing dynamic soft materials. Abstract : A visible light induced dynamic mechanical bond (DMB) has been constructed. The photoinduced dynamic bonding behaviors enabled the fabrication of a DMB‐cross‐linked dynamic polymeric gel.